Evidence that non-lipid cardiovascular risk factors are associated with high prevalence of coronary artery disease in patients with heterozygous familial hypercholesterolemia or familial combined hyperlipidemia. - Skoumas, I; Masoura, C; Pitsavos, C; Tousoulis, D; Papadimitriou, L; Aznaouridis, K; Chrysohoou, C; Giotsas, N; Toutouza, M; Tentolouris, C; Antoniades, C; Stefanadis, C (2007)
BACKGROUND: Heterozygous familial hypercholesterolemia (hFH) and familial combined hyperlipidemia (FCH) have been associated with increased risk for coronary artery disease (CAD), but the impact of traditional risk factors to the incidence of CAD in these patients remains unknown. The present study evaluates the contribution of such risk factors to the development of CAD in these two dyslipidemic populations. METHODS: This cross-sectional study enrolled a total 1306 subjects; 600 individuals with hFH (mean age 41+/-13 years, 261 males and 339 females), and 706 individuals with FCH (mean age 49+/-11 years, 463 males and 243 females). Blood samples were collected after 12 hours fasting period, and serum lipids were determined. Multivariate logistic regression models were used to estimate the odds ratios of CAD based on the type of hyperlipidemia, after adjustment for demographic characteristics and risk factors. RESULTS: Subjects with FCH were older (P<0.001), and they had a significantly increased prevalence of hypertension, diabetes and metabolic syndrome (40 vs. 10%, 13 vs. 2% and 41 vs. 6% respectively, all P<0.001) compared to the hFH group. Total cholesterol, LDL-cholesterol, and apolipoprotein B levels were higher (all P<0.001) in hFH subjects. Although in multivariate analysis lipid abnormalities found in hFH were associated with increased risk of CAD (P<0.001) compared with lipid abnormalities of FCH, the overall prevalence of CAD was similar between the two groups (16.7 vs. 15.3%, P=NS). CONCLUSIONS: Despite the high atherogenic potential of altered lipid metabolism found in hFH, the prevalence of CAD is similarly increased in patients with hFH or FCH. This may be related to the clustering of non-lipid cardiovascular risk factors, such as diabetes mellitus, observed in patients with FCH.